PEMBELAJARAN REKA CERITA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENULIS NASKAH DRAMA - Hani Dwi Anzani (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
This research is motivated by the problems that arise during the learning playwriting class XI IPA 4 SMAN 4 Bandung. The purpose of this study was to describe the results of learning playwriting through their learning techniques picture story. This classroom action research conducted in two cycles. Technique of design story picture was learning story telling based on a picture. The picture shows an activity that reflects a particular purpose or idea. This research was conducted in SMAN 4 Bandung with research subjects in class XI IPA 4 totaling 44 students. Researchers describe objectively the problems of learning in the classroom concerning repairs, upgrades, and classroom management. The results showed an increase in students' ability to write a play. In the first cycle of students 'average score was 70.5 and the second cycle students' average score increased to 84.25. Value of students in the second cycle has been reached minimum criteria graduation (KKM). This shows that students are able to write a script well and their design picture stories technique suitable for use in learning playwriting.Keywords: playwriting, design story picture technique, classroom action research